PENGARUH PENGENDALIAN INTERN, PEMANFAATAN TEKNOLOGI INFORMASI DAN MOTIVASI KERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi pada Organisasi Perangkat Daerah Kabupaten Rokan Hulu) - Apriani Fitri; Agusti Restu; Lukman Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to measure the internal influence, information technology and work motivation on the performance accountability of the government in Rokan Hulu Regency. The sampling technique used purposive sampling. Respondents who were sampled in this study were the Head of OPD, the OPD Secretary, the Head of the Subdivision of Evaluation and Reporting Planning, as well as the Head of the Finance Subdivision in the Hulu Rokan Regional Apparatus Organization. Data analysis using multiple linear regression analysis techniques using SPSS 20.0. Respondents in this study may be 116 respondents. The results of this study indicate that information and work motivation have an effect on the performance accountability of government agencies in Rokan Hulu Regency with a management value of 0.000 <0.05, the use of information technology with a value of 0.002 <0.05, and work motivation with a sig value of 0.048 <0,05. The coefficient of determination can provide an explanation that 44.9% of government performance accountability is influenced by the use of information technology, work motivation), while 56.1% of company accountability.Keywords: Performance Accountability of Government Agencies, Internal Control, Utilization of Information Technology and Work Motivation